(untitled) (Innovative professional education, 2024)
The considers the need to create a system of counseling on youth entrepreneurship in VET institutions in the paradigm of socio-economic development with an emphasis on the transition to a multi-level counseling system. The advantages of such counseling with the possibility of choosing programs for providing counseling services are analyzed. It is proposed to apply the diversification of counseling in VET institutions to create an integrated approach to training specialists.